Educational and methodological manual for conducting laboratory classes on special epizootology on infectious diseases common to several species of animals - Кісера, Я. В.; Божик, Л. Я.; Мартинів, Ю. В. (Сполом, 2023)
The educational and methodological manual presents material on 24 diseases: anthrax, tuberculosis, brucellosis, leptospirosis, listeriosis, tetanus, pasteurellosis, necrobacteriosis, hoof-rot, botulism, tularemia, rabies, Aujeski's disease, foot-and-mouth disease, smallpox, chlamydia (enzootic abortion of sheep, chlamydia pigs, chlamydia of livestock), rickettsiosis (Q-fever, infectious hydropericarditis, infectious keratoconjunctivitis), trichophytosis, microsporia. Issues of diagnosis, treatment, immunoprophylaxis, general prevention and control measures are highlighted. Представлений матеріал по 24 захворюваннях: сибірці, туберкульозу, бруцельозу, лептоспірозу, лістеріозу, правцю, пастерельозу, некробактеріозу, копитній гнилизні, ботулізмі, туляремії, сказу, хвороби Ауєскі, ящуру, віспі, хламідіозах (ензоотичний аборт овець, хламідіоз свиней, хламідіоз худоби), рикетсіозах (ку-гарячка, інфекційний гідроперикардит, інфекційний кератокон’юнктивіт), трихофітії, мікроспорії. Висвітлені питання діагностики, лікування, імунопрофілактики, загальної профілактики та заходи боротьби.
Keywords: інфекційні хвороби тварин; епізоотологія